Contesting the Meaning of Intergroup Disadvantage: Towards a Psychology of Resistance. (September 2015) - Leach, Colin Wayne; Livingstone, Andrew G.; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> A prevailing view in psychology is that intergroup disadvantage poses a serious threat to psychological well‐being. Lower self‐esteem and out‐group favoritism are two of the most examined forms of psychological damage thought to follow from intergroup disadvantage. We review theory and research on lower self‐esteem and out‐group favoritism with close attention to the nature of the evidence suggesting that intergroup disadvantage is detrimental psychologically. We argue that this evidence is not as strong or unambiguous as is widely believed. This has likely led to an underestimation of psychological resistance to disadvantage—that middle ground between the extremes of surviving at subsistence levels of psychological well‐being and confronting disadvantage. We propose that greater attention to the psychological meaning that the disadvantaged give their position enables a more accurate assessment of the diverse forms of psychological resistance to intergroup disadvantage.